A Robust, Real-Time and Calibration-Free Lane Departure Warning System - Gamal, Islam; Badawy, Abdulrahman; Al-Habal, Awab M.W; Adawy, Mohammed E.K; Khalil, Keroles K.; El-Moursy, Magdy A.; Khattab, Ahmed (IEEE International Symposium on Circuits and Systems proceedings, 2019)
A real-time and calibration-free lane departure warning system algorithm is proposed. The pre-processing stage of the lane departure algorithm is carried out using Gaussian pyramid to smooth the image and reduce its dimensions, which decreases the unnecessary details in the image. A lane detection stage is then developed based on the Edge Drawing Lines (EDLines) algorithm that is a real-time line segment detector, which has false detection control. The reference-counting technique is used to track the lane boundaries and predict the missing ones. Experimental results show that the proposed algorithm has accuracy of 99.25% and average processing time of 80 fps (frame per second). The proposed algorithm is efficient to be used in the self-driving systems in the Original Equipment Manufacturers (OEMs) cars.